Struktur Batin dalam Puisi “Tuhan, Aku Cinta Padamu” Karya W.S Rendra, dan “Dongeng Kucing” Karya Sapardi Djoko Damono - Azzahra, Mira Nusantriani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The aim of this research is to further explore how the themes of divinity, life and even death are presented in contemporary poetry. The main focus is on the analysis of the inner structure, language style, and symbolism used by poets to express the concepts of divinity, death, and life experiences. In particular, this journal will discuss how poetry with themes of divinity, death and life values can be a reflection of individual spiritual struggles, as well as a medium for conveying moral messages that are relevant to the challenges of the times. With a qualitative approach and a semiotic approach, it is hoped that this research can provide a new contribution in understanding the dynamics of religious poetry and its relevance in the context of modern life. The method used in this research is a qualitative descriptive method with a semiotic approach according to the views of Charles Sanders Peirce, an American philosopher, namely analyzing poetic texts based on the ideas and signs or symbols contained in the poetic texts to be studied. This research uses the object of study, namely, the poem